2013
DOI: 10.1021/cn4001878
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of ROS Insults by Streptomyces Secondary Metabolites in Primary Cortical Neurons

Abstract: Oxidative stress is a common point in neurodegenerative diseases, widely connected with mitochondrial dysfunction. In this study, we screened seven natural products from Streptomyces sources against hydrogen peroxide insult in primary cortical neurons, an oxidative stress in vitro model. We showed the ability of these compounds to inhibit neuronal cytotoxicity and to reduce ROS release after 12 h treatment. Among the tested compounds, the quinone anhydroexfoliamycin and the red pyrrole-type pigment undecylprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 56 publications
1
33
0
Order By: Relevance
“…The activation of Nrf2 is shown to inhibit the effect of the mitochondrial uncoupler carbonyl cyanide-4-(trifluoromethoxy)phenylhydrazone (FCCP) on cytoplasmic Ca 2+ ions, which in turn, enhances the mitochondrial function, inhibited the production of ROS and increased the levels of antioxidant enzymes (Leirós et al 2013).…”
Section: Ischaemia and Strokementioning
confidence: 99%
“…The activation of Nrf2 is shown to inhibit the effect of the mitochondrial uncoupler carbonyl cyanide-4-(trifluoromethoxy)phenylhydrazone (FCCP) on cytoplasmic Ca 2+ ions, which in turn, enhances the mitochondrial function, inhibited the production of ROS and increased the levels of antioxidant enzymes (Leirós et al 2013).…”
Section: Ischaemia and Strokementioning
confidence: 99%
“…Moreover, the metabolites derived from Streptomyces are described as potent protective agents in neuronal cells against oxidative stress induced damage. In fact, a recent study by Leiros et al ( 2013 ) has identified seven bioactive compounds produced by Streptomyces sp. which protects against hydrogen peroxide (H 2 O 2 ) challenge in primary cortical neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that two compounds, the quinone anhydroexfoliamycin and the red pyrrole‐type pigment n‐decylprodigiosin, improved mitochondrial function, increased the antioxidant enzymes, and decreased reactive oxygen species (ROS) levels and caspase‐3 apoptotic activity in primary cortical neurons. Anhydroexfoliamycin also has been reported to induce Nrf2 nuclear translocation and affect the Nrf2‐ARE pathway (Leirós et al, ).…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Anhydroexfoliamycin also has been reported to induce Nrf2 nuclear translocation and affect the Nrf2-ARE pathway (Leirós et al, 2014).…”
Section: Introductionmentioning
confidence: 99%